Functional Hydration Behavior: Interrelation between Hydration and Molecular Properties at Lipid Membrane Interfaces - Nozomi Watanabe; Keishi Suga; Hiroshi Umakoshi (Journal of Chemistry)
Water is an abundant commodity and has various important functions. It stabilizes the structure of biological macromolecules, controls biochemical activities, and regulates interfacial/intermolecular interactions. Common aspects of interfacial water can be obtained by overviewing fundamental functions and properties at different temporal and spatial scales. It is important to understand the hydrogen bonding and structural properties of water and to evaluate the individual molecular species having different hydration properties. Water molecules form hydrogen bonds with biomolecules and contribute to the adjustment of their properties, such as surface charge, hydrophilicity, and structural flexibility. In this review, the fundamental properties of water molecules and the methods used for the analyses of water dynamics are summarized. In particular, the interrelation between the hydration properties, determined by molecules, and the properties of molecules, determined by their hydration properties, are discussed using the lipid membrane as an example. Accordingly, interesting water functions are introduced that provide beneficial information in the fields of biochemistry, medicine, and food chemistry.